Efforts to Instill an Attitude of Tolerance Through Multicultural Education in Indonesian History Subjects - Oktavia Wahyuni Saputri; Utami, Indah Wahyu Puji; Sayono, Joko (Universitas Islam Malang, 2024)
Multicultural education is not just about tolerance, but also about strengthening national unity and unity. By understanding and appreciating diversity, Indonesian children will develop into inclusive individuals, respectful of each other, and have a deep love of their homeland. Multicultural education is hoped that it can foster an attitude of tolerance in students at school, and multicultural education can be integrated into history learning at school. This research analyzes multicultural values in Indonesian history subjects on students' attitudes toward tolerance. The research method used is a literature study. The research results show that history subjects have an important role in fostering an attitude of tolerance in students through the dimensions of multicultural education